Investigation of carbon black grades and multiwall carbon nanotube hybridization for the development of electrically conductive polyamide 6-based nanocomposite filaments - Kaplan, Müslüm (İdris Karagöz, 2025)
The development of electrically conductive polymer filaments has gained significant attention for applications in smart textiles and flexible electronics. This study systematically investigates the influence of different carbon black (CB) grades and their hybridization with multiwall carbon nanotubes (MWCNTs) on the electrical and processing properties of polyamide 6 (PA6) based nanocomposite filaments. Three commercial CB grades were evaluated through morphological analysis, mixing energy measurements, and electrical resistivity characterization. Light microscopy analysis revealed that Vulcan XC72 exhibited superior dispersion homogeneity compared to XC MAX22 and XC615. The mixing energy calculations demonstrated that XC72 maintained consistent processing behavior, with energy requirements ranging from 25.067 J/cm³ at 1 wt% to 25.790 J/cm³ at 5 wt% loading. Electrical resistivity measurements showed significant differences in percolation behavior, with XC72 achieving 2.33E+03 ohm·cm at 13 wt%. Based on these findings, XC72 was selected for developing PA6/CB and PA6/MWCNT/CB hybrid nanocomposite filaments. While PA6/CB filaments showed insufficient conductivity, PA6/MWCNT filaments achieved 2.94E+00 ohm·cm at 10 wt%, and hybrid filaments demonstrated intermediate conductivity of 7.28E+00 ohm·cm. SEM analysis revealed the formation of interconnected networks where MWCNTs effectively bridged CB particles, explaining the enhanced conductivity of hybrid systems. This study provides crucial insights for developing cost-effective conductive polymer filaments through systematic filler selection and processing optimization.

The development of electrically conductive polymer filaments has gained significant attention for applications in smart textiles and flexible electronics. This study systematically investigates the influence of different carbon black (CB) grades and their hybridization with multiwall carbon nanotubes (MWCNTs) on the electrical and processing properties of polyamide 6 (PA6) based nanocomposite filaments. Three commercial CB grades were evaluated through morphological analysis, mixing energy measurements, and electrical resistivity characterization. Light microscopy analysis revealed that Vulcan XC72 exhibited superior dispersion homogeneity compared to XC MAX22 and XC615. The mixing energy calculations demonstrated that XC72 maintained consistent processing behavior, with energy requirements ranging from 25.067 J/cm³ at 1 wt% to 25.790 J/cm³ at 5 wt% loading. Electrical resistivity measurements showed significant differences in percolation behavior, with XC72 achieving 2.33E+03 ohm·cm at 13 wt%. Based on these findings, XC72 was selected for developing PA6/CB and PA6/MWCNT/CB hybrid nanocomposite filaments. While PA6/CB filaments showed insufficient conductivity, PA6/MWCNT filaments achieved 2.94E+00 ohm·cm at 10 wt%, and hybrid filaments demonstrated intermediate conductivity of 7.28E+00 ohm·cm. SEM analysis revealed the formation of interconnected networks where MWCNTs effectively bridged CB particles, explaining the enhanced conductivity of hybrid systems. This study provides crucial insights for developing cost-effective conductive polymer filaments through systematic filler selection and processing optimization.
Investigation of carbon black grades and multiwall carbon nanotube hybridization for the development of electrically conductive polyamide 6-based nanocomposite filaments
Keywords: Wearable Materials; Giyilebilir Malzemeler [EN] Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler [EN] Polymers and Plastics; Polimerler ve Plastikler [EN] Fiber Technology; Lif Teknolojisi